2018
DOI: 10.4103/jpbs.jpbs_225_17
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the anticancer activity of the gemcitabine and doxorubicin combined in a nanoemulsion

Abstract: Context:Doxorubicin (DOX) and gemcitabine (GEM) are anticancer drugs that were combined in a nanoemulsion (NE) to reduce their adverse side effects.Aim:To detect the antitumor activity of the combination formulas of GEM and DOX, loaded either in water (GEM+DOX-Sol) or in NEs (GEM–DOX combination/loaded NE [GEM+DOX/LNE]), in female Swiss albino mice inoculated with Ehrlich ascites carcinoma (EAC).Settings and Design:The anticancer assessment of the NE formulas was implemented in 200 mice, which were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…), GPIII: DOX group (MCF-7 cells and DOX (2 mg/Kg; i.p.) [ 85 ] once every 3 days, GPIV: CQ group (MCF-7 cells and CQ (50 mg/Kg; i.p.) [ 19 ] once every three days.…”
Section: Methodsmentioning
confidence: 99%
“…), GPIII: DOX group (MCF-7 cells and DOX (2 mg/Kg; i.p.) [ 85 ] once every 3 days, GPIV: CQ group (MCF-7 cells and CQ (50 mg/Kg; i.p.) [ 19 ] once every three days.…”
Section: Methodsmentioning
confidence: 99%
“…By binding and stabilizing microtubules, docetaxel prevents mitotic spindle assembly and thus blocks cell cycle progression in late G2-M phase (Yvon et al, 1999;Morse et al, 2005). Chemotherapy agents affect HDL metabolism in varying ways: docetaxel increases HDL and decrease TG levels in the serum of mice bearing Ehrlich tumor (Alkhatib et al, 2017), but doxorubicin decreases HDL biogenesis by reducing the expression of ABCA1 and apoA-I, while cyclophosphamide and paclitaxel show no significant effect on HDL biogenesis (Sharma et al, 2016). Although there is no study investigating the effect of docetaxel monotherapy on lipid metabolism in humans, our discovery of docetaxel as a potent promoter of HDL biogenesis (Figures 3, 5) suggests that docetaxel may be repurposed for the treatment of ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin is an effective anti-biotic and anti-tumor drug. It has been formulated for the treatment of liver and kidney carcinoma besides to breast cancer metastasis ( Alkhatib et al, 2018 ). Accordingly, these findings reported that DOX treatment resulted in inhibition of the hepatic metastasis.…”
Section: Discussionmentioning
confidence: 99%